The Effects of the U.S. MFA on Small Exporters - Dean, Judith M. (The Review of Economics and Statistics, 1990)
This paper tests two hypotheses regarding the impact of the U.S. Multifiber Arrangement restrictions on developing countries' exports of textiles and clothing to the United States: that the Multifibre Arrangement is a binding constraint on exporters; and that the arrangement encourages the growth of smaller exporters by restricting exports from major sellers. Pooled data on eight small Asian exporters over the period 1975-84 is used. Results strongly support the hypothesis that the Multifibre Arrangement has been a binding constraint. Although the arrangement appears to have diverted demand toward these smaller sellers, this effect is counteracted by slow growth in their own restraints. Copyright 1990 by MIT Press.